2019
DOI: 10.3390/universe5120221
|View full text |Cite
|
Sign up to set email alerts
|

Towards a Fisher-Information Description of Complexity in de Sitter Universe

Abstract: Recent developments on holography and quantum information physics suggest that quantum information theory has come to play a fundamental role in understanding quantum gravity.Cosmology, on the other hand, plays a significant role in testing quantum gravity effects. How to apply this idea to a realistic universe is still unknown. Here, we show that some concepts in quantum information theory have cosmological descriptions. Particularly, we show that the complexity of a tensor network can be regarded as a Fisher… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…This conjecture was demonstrated in Ref. [28]. However, machine learning is also related to the tensor network through renormalization in condensed matter physics [31] and possibly has significant holographic meaning [32,33].…”
Section: Qsat K − S Atmentioning
confidence: 86%
See 1 more Smart Citation
“…This conjecture was demonstrated in Ref. [28]. However, machine learning is also related to the tensor network through renormalization in condensed matter physics [31] and possibly has significant holographic meaning [32,33].…”
Section: Qsat K − S Atmentioning
confidence: 86%
“…χ → ∞ Fortunately, recent work from Hastingss [28] demonstrated that this conjecture is "asymptotically" true in the limit as . Hence, the ratio of the QMF to the QMC χ QMF(G, χ, O) χ converges to one as tends to infinity.…”
Section: Large C Limitmentioning
confidence: 98%
“…Hence, Quantum Metrology not only refines precision measurement but it also provides fresh avenues of probes which are otherwise inaccessible. The technique of fisher information has previously been used in various different models for studying the dynamics of systems in curved spacetime [18][19][20] The precision of parameter estimation is measured by Fisher information [22]. In the field of parameter estimation, the prime focus is to give an estimate of the values of the unknown physical parameters labelling a quantum mechanical model and to enhance the precision of resolution.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, increasing evidences show that it may play a crucial role in the understanding the nature of space-time [6,7]. In particular, as implied by the holographic entanglement entropy [8,9], there is a fundamental connection between quantum information theory and gravitational physics [10][11][12][13][14][15][16][17][18]. The quantum complexity is another significant concept of the connection and thus has attracted a lot of attention in the past few years.…”
Section: Introductionmentioning
confidence: 99%